2018
DOI: 10.1038/s41598-018-21468-w
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Bushen-Yizhi Formula as a Therapeutic Agent against Alzheimer’s Disease

Abstract: Bushen-Yizhi prescription (BSYZ) has been an effective traditional Chinese medicine (TCM) prescription in treating Alzheimer’s disease (AD) for hundreds of years. However, the underlying mechanisms have not been fully elucidated yet. In this work, a systems pharmacology approach was developed to reveal the underlying molecular mechanisms of BSYZ in treating AD. First, we obtained 329 candidate compounds of BSYZ by in silico ADME/T filter analysis and 138 AD-related targets were predicted by our in-house WEGA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…(Fang et al, 2017a;Fang et al, 2019). In recent years, systems pharmacology-based approaches have provided new insights into elucidating the mechanisms of TCM in the treatment of diseases such as cardiovascular diseases and AD (Zhou and Wang, 2014;Fang et al, 2017a;Cai et al, 2018). In this study, we employed a systems pharmacology approach to identify potential compounds, candidate targets, and therapeutic mechanisms of KXS against AD disease from a holistic prospect (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…(Fang et al, 2017a;Fang et al, 2019). In recent years, systems pharmacology-based approaches have provided new insights into elucidating the mechanisms of TCM in the treatment of diseases such as cardiovascular diseases and AD (Zhou and Wang, 2014;Fang et al, 2017a;Cai et al, 2018). In this study, we employed a systems pharmacology approach to identify potential compounds, candidate targets, and therapeutic mechanisms of KXS against AD disease from a holistic prospect (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, BSYZ also increased the percentage of alternation in Y-maze at the same time. That might be associated with the treatment effects of BSYZ on learn and memory deficits related diseases [ 23 , 24 , 26 ]. Consistent with these data, the mice with MPTP treatment also exhibited obviously dopaminergic neuronal degeneration with decreased TH-positive cells and Nissl positive staining neurons in SNpc area.…”
Section: Discussionmentioning
confidence: 99%
“…BSYZ, a traditional Chinese medicine, is composed of common Cnidium fruit, tree peony bark, ginseng root, Radix Polygoni Multiflori Preparata, Barbary wolfberry fruit, and Fructus Ligustri Lucidi. Our previous studies have confirmed that BSYZ has extensive neuroprotective effects such as antisenesce, antiapoptosis, and alleviation of oxidative stress in various Alzheimer's disease (AD) animal models [ 23 26 ]. Our recent investigation further demonstrated BSYZ is effective in reducing age-related neurodegenerative disorders via antineuroinflammation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology, as a novel strategy to identify the active compounds of herbs and their therapeutic targets, was first proposed by Professor Hopkins [6] and has increasingly become a tool to systematically reveal the function of a complex biological system [7,8], which coincides with the overall concept of TCM and provides a new approach to explore the pharmacological mechanism of TCMs [9,10].…”
Section: Introductionmentioning
confidence: 99%